A non-noble metal supported catalyst with potential prospect for hydroisomerization of n-hexadecane: Second metal incorporated NiMe/SAPO-11 catalyst with superior hydroisomerization performance. (15th September 2022) - Dai, Xiaojun; Cheng, Yan; Si, Meng; Wei, Qiang; Huang, Wenbin; Yang, Han; Zhou, Yasong
Graphical abstract: Highlights: The bimetal supported catalysts NiMe/SAPO-11 were prepared with La, Ga, Ce and Zr as the second metal additives, respectively. The second metal additives formed alloy compounds with the main metal Ni. NiGa/SAPO-11 showed the best catalytic performance for the hydroisomerization of n-hexadecane and was comparable to Pt/SAPO-11. It provides a new strategy for preparing high-efficiency and low-cost non-noble metal supported catalysts for the hydroisomerization of long-chain n-alkanes. Abstract: Aiming at the problems of high cost and high sensitivity to sulfur compounds in the raw materials of the noble metal supported hydroisomerization catalysts, this paper proposed preparing a series of bimetallic supported catalysts (NiMe/SAPO-11) with Ni as the main metal and non-noble metals (La, Ga, Ce and Zr) as the second metal additives for the hydroisomerization of n-hexadecane. A series of physicochemical characterization results showed that the introduction of the second metal additive reduced the acid amount and mesoporous volume of the bimetallic supported catalysts. However, the second metal additive weakened the interaction between the metal active phase and the supports, and promoted more Ni species to form hydrogenation/dehydrogenation active phases. The results of HRTEM and XPS show that the electrons in the d conduction band of the second metal additive can be transferred to the electron vacancy in the 3d conduction band of Ni, thus forming alloy compounds. The second metal additive played the role of "diluting" the Ni species, reducing the particle size of the metal active phase, thus greatly improving the catalytic performance of NiMe/SAPO-11. The catalytic performance of NiGa/SAPO-11 was the best, with a maximum yield of i-hexadecane of 64.90%, which is comparable to the maximum yield of i-hexadecane of 68.80% for the hydroisomerization of n-hexadecane catalyzed by Pt/SAPO-11. This is expected to provide a new strategy for the preparation of low-cost and efficient catalysts for the hydroisomerization of n-alkanes.